Valuasi Ekonomi Kawasan Karst Desa Jatijajar Kecamatan Ayah Kabupaten Kebumen - Rasyid Wisnuaji; Muhamad Rijal Pamungkas (Jurnal Social Economic of Agriculture, 2022)
Jatijajar Village which is included in the Gombong karst area in accordance with the Minister of Energy and Mineral Resources Decree No. 3043 K / 40 / MEM / 2014 and confirmed by the Kebumen Regency Regional Regulation No. 23 of 2012 concerning RTRW of Kebumen Regency for 2011 - 2013. Karst is a landscape of the karstification process of carbonate rock (CaCO3) which is deposited after passing through the available geological space and time. Karst has a distinctive hydrological condition due to the dissolution of carbonate rock due to the physical properties of limestone which is easily soluble and has secondary porosity so that it cannot store water for a long time. Rainwater that flushes the karst area directly falls to the bottom of the water-saturated zone and then flows through cracks and large passageways (caves) such as canals to springs exit points or is directly dumped into the sea, only a small amount flows on the surface. Until now, it has the potential value of environmental services (environmental services) and ecological services both in the karst area itself and in the non-karst area which is used as a buffer zone. The underground river system that is formed in the karst area provides benefits to the environment around the karst area and even the community as a provider of clean water needs that are perennial / flowing throughout the season. Characteristics of natural resources in the Karst Gombong area of Jatijajar Village have resource characteristics in the form of direct use, namely from the existence of a water hydrological system from the karst area which consists of the value of water resource utilization which is used to meet household needs, the value of water resources for lowland rice farming, and Water Resources from underground rivers in the karst area are 15 springs. The total economic value of the potential use of existing resources in the Gombong Karst Gombong area of Jatijajar Village is IDR 87,616,789,519 in one year. The magnitude of this value is the value of natural and environmental resources from the direct use of the availability of natural resources to the community. These values will be lost if the karst area is damaged either from mining activities or changes in environmental functions. In fact, this value will be a value that must be spent by the community in order to compensate for the loss of potential natural resources in the karst area